P PENGUATAN PERAN BUMNAG SEBAGAI UNTUK MENINGKATKAN PENDAPATAN NAGARI DAN MASYARAKAT SAKO PASIA TALANG KECAMATAN SUNGAI PAGU KABUPATEN SOLOK SELATAN: Participatory Institutional Strengthening of Village-Owned Enterprises to Promote Community Economic Development - Sosmiarti Sosmiarti; Fadhil Aptana Sadjiana; Ferry Lismanto Syaiful; Yuliati Shafan Nur; Andani Eka Putra (BULETIN ILMIAH NAGARI MEMBANGUN, 2026)
Village-Owned Enterprises (VOEs) play a strategic role in promoting local economic development and improving community welfare in rural Indonesia. However, many VOEs, including VOEs Sako Jaya in Sako Pasia Talang Village, South Solok Regency, face persistent challenges, including weak institutional governance, limited human resource capacity, inadequate access to capital, and weak stakeholder collaboration. This study aimed to identify the institutional potential and challenges of VOEs Sako Jaya and strengthen its institutional capacity through a participatory, multi-stakeholder approach. A community-based participatory approach was implemented through preliminary surveys, field observations, focus group discussions, participatory workshops, mentoring, and monitoring and evaluation. Data were analyzed using descriptive qualitative methods based on observations, documentation, and group discussions. The study involved VOEs managers, village government officials, MSME actors, academics, local government representatives, and private-sector partners. A total of 56 participants from nine villages, nine VOEs, and twelve MSMEs were involved. The findings identified three major institutional challenges: limited human resource capacity, inadequate business capital, and weak organizational governance and coordination. An institutional strengthening plan was subsequently developed, broiler chicken farming was selected as the priority business based on local potential and market demand, and a tripartite partnership involving the South Solok Regency Government, Universitas Andalas, and Supreme Energy was established to support financing, capacity building, and technical assistance. Overall, the participatory approach effectively strengthened institutional capacity, expanded strategic partnerships, and enhanced organizational readiness for sustainable rural enterprise development, providing a replicable model for strengthening village-owned enterprises and promoting community economic development.